Sørena Kierkegaarda koncepcja grzechu i winy - Gazda, Paweł (Warszawskie Studia Teologiczne, 2022)
The aim of this work is to analyze the concept of sin in the works of Søren Kierkegaard. A sensible analyze can’t ignore what Kierkegaard wrote about sin primarily in: The Concept of Anxiety, The Sickness Unto Death, Philosophical Fragments and Concluding Unscientific Postscript to Philosophical Fragments. Therefore: the discussion of the concept of sin will begin with a review of the traditional concept of Original Sin. Subsequently, the concept of First Sin will be presented, and then further specified by its juxtaposition with the concept of guilt. The study will be closed with a discussion of the analysis of Johannes Climacus from Concluding Unscientific Postscript to Philosophical Fragments – capturing the categories of guilt and sin in the context of the concept of truth.